Evaluation of irrigated rice (Oryza sativa L.) varieties under irrigation condition at Dasenech Distinct, South Omo Zone (International Journal of Agricultural Research, Innovation and Technology, 2023)
Rice crop is essential in a country. Still, the production and productivity are low due to uncovering a suitable area for rice production and the shortage of improved and unedited well-adapted variety. To solve this problem, the study was conducted in Dasenech district during (2020/21 and 2021/22) cropping seasons to select well-adapted varieties. The study contains 6 varieties (Gode, Shebele, Chewaqa, Kallafo, Nerica-15, and Pawe-2). For this study used a randomized complete block design with three replications. Yield and other trait data were collected and subjected to analysis of variance. The result of the analysis of variance showed that all parameters were significantly affected among tested rice varieties. The Pawe-2 variety gave the highest grain production (6284.7 kg ha-1) among the tested varieties.  Based on the study result, it can be suggested that variety Pawe-2 perform well and is suitable for agro-pastoral in the Dasenech area under irrigation condition and its similar agro-ecology.Int. J. Agril. Res. Innov. Tech. 13(1): 38-41, June 2023